Flying to the moon : an astronaut's story - Collins, Michael, 1930-2021- (Farrar Straus Giroux, 2019)
Astronaut Michael Collins adds a revised chapter to the extraordinary story of his training and participation in the Gemini 10 and Apollo 11 flights.